Ações da adição de Morinda citrifolia (Noni) sobre os aspectos celulares e moleculares de complexos cumulus-oócito (CCOS) bovinos durante maturação in vitro - Souza, Breno Glaessner Gomes Fernandes (2019)
The improvement in reproductive efficiency in the Brazilian cattle herd has a significant economic impact. The in vitro production of embryos is a biotechnology widely used in Brazil that allows the increase of animals per year through the transfer of embryos obtained in the laboratory. However, excessive production of oxygen reactive species by the technique results in cellular damage to oocytes and embryos, leading to apoptosis due to oxidative stress. The use of antioxidants during in vitro maturation, fertilization and cultivation processes reduces the effects of oxygen reactive species. The antioxidant properties of Morinda citrifolia fruits are due to the presence of substances such as phenolic compounds, especially quercetin. The objective of this research is to evaluate the effects of Morinda citrifolia on the cellular and molecular aspects of the in vitro maturation stage of bovine oocytes. A total of 817 viable oocytes were obtained for in vitro maturation, distributed for treatments with Morinda citrifolia and control groups. After the maturation stage, the rate of oocytes matured by the Hoescht 33342 technique was determined. Some oocytes were evaluated for apoptosis genes, genes for measuring the antioxidant action of Morinda citrifolia and oxidative stress through mRNA expression in the technique of qRT-PCR. The data from research one indicate that Morinda citrifolia has antiapoptotic effect during in vitro maturation.